Education on the Importance of Diet Pattern Settings and Implementation Juice Star Shine for Hypertension Sufferers - Damawiyah, Siti; Wijayanti, Lono; Nadatien, Ima (UNUSA Press, 2024)
Hypertension is the number one cause of death in the world every year. Hypertension is now a major problem for all of us, not only in Indonesia but in the world, because hypertension is one of the entry points or risk factors for diseases such as heart disease, kidney failure, diabetes, stroke. The problems that will be addressed in this community service program are increasing public knowledge about the importance of regulating diet and implementing or providing star shine juice for hypertension sufferers in Kebonsari Village, Surabaya. The method used is to gather patients and/or their families then provide health education and conduct blood pressure checks. Education and training use lecture methods, questions and answers and direct demonstrations. A pre- test is conducted before education and training are given. Meanwhile, to determine the increase in respondent knowledge, it can be determined by comparing the results of the post-test with the results of the pre-test. The level of knowledge of hypertension sufferers and their families increased after being given health education on the management of hypertension which includes regulating diet and implementing or giving star shine juice. Sufferers and their families have been able to make star shine juice as a health drink to lower high blood pressure. The outputs of this community service activity are reports that have been published in national journals, online or offline mass media, HAKI, and reports on improving community capabilities.